Best practices for a successful MNCH partnership that an external evaluation could never find: Experiences from the Maternal and Child Health Integrated Program. (June 2015) - Agarwal, Koki; Caiola, Nancy; Gibson, Anita
Abstract: Partnerships for maternal, newborn, and child health (MNCH) are increasingly prevalent, yet little has been published about the possible reasons for their success or failure. In this commentary, we assess the presence of four principles for a successful collaborative partnership—clear goals, clear roles, trust, and commitment—within the Maternal and Child Health Integrated Program (MCHIP), an MNCH partnership among eight implementing organizations that was funded by USAID from 2008 to 2014. MCHIP made substantial strides in developing clear goals and partner roles, and despite external constraints, to develop the trust and commitment needed to work in an interdependent manner. Future collaborative MNCH partnerships should pursue a shared understanding of these four principles as early and often as possible to ensure success.